THE PERCEPTION OF POST-PARTUM WOMEN WITH HIV / AIDS ABOUT PSYCHOSOCIAL SUPPORT IN BANDUNG CITY - Nunung Nurhayati; Lia Juniarni; Mimin Sumiati (Journal of Maternity Care and Reproductive Health, 2019)
About 17 million women around the world aged 15-49 years are infected with HIV and AIDS. HIV / AIDS is transmitted from mother to baby during pregnancy, intra-natal, postnatal and it is a cause of death. In 2015, HIV transmission occurred in more than 38,500 children born to HIV-positive women. Transmission of HIV / AIDS from mother to baby during labor can be prevented by ARV therapy. The psychological aspects of postpartum women with HIV / AIDS include fear, shame, and a higher risk of depression compared to normal postpartum. Social support is needed by individuals in the situation. The participants in this study were 6 people. The sampling technique used purposive sampling with the inclusion criteria for post-partum women with HIV / AIDS who routinely controlled treatment. The results of the study found the theme of psychosocial support from the closest person consisted of 3 categories, namely psychological support from the family, support from fellow friends with HIV / AIDS and support in undergoing treatment. Conclusions from the results of the study found new insights that post-partum women with HIV / AIDS had accumulated feeling from the process of HIV / AIDS. Support is needed from the people closest to the family and support from fellow friends with HIV / AIDS, to prevent continuing into the desperation stage that results in death.Keywords: HIV / AIDS, Physiological support, Perception, postpartum-women.